Treatment of Branch Retinal Vein Occlusion induced Macular Edema with Bevacizumab - Abegg, Mathias (BioMed Central, 2008)
BACKGROUND: Branch retinal vein occlusion is a frequent cause of visual loss with currently insufficient treatment options. We evaluate the effect of Bevacizumab (Avastin(®)) treatment in patients with macular edema induced by branch retinal vein occlusion. METHODS: Retrospective analysis of 32 eyes in 32 patients with fluorescein angiography proven branch retinal vein occlusion, macular edema and Bevacizumab treatment. Outcome measures were best corrected visual acuity in logMAR and central retinal thickness in OCT. RESULTS: Visual acuity was significantly better 4 to 6 weeks after Bevacizumab treatment compared to visual acuity prior to treatment (before 0.7 ± 0.3 and after 0.5 ± 0.3; mean ± standard deviation; p < 0.01, paired t-test). Gain in visual acuity was accompanied by a significant decrease in retinal thickness (454 ± 117 to 305 ± 129 μm, p < 0.01, paired t-test). Follow up (170, 27 – 418 days; median, range) shows that improvement for both visual acuity and retinal thickness last for several months after Bevacizumab use. CONCLUSION: We present evidence that intravitreal Bevacizumab is an effective and lasting treatment for macular edema after branch retinal vein occlusion.